IMPLEMENTATION OF THE HAVERSINE FORMULA IN THE WEBGIS OF PRIVATE UNIVERSITIES IN WEST JAVA AND BANTEN - Hasanah, Nurul Islam; Somantri, Somantri; Sujjada, Alun (IDEALIS : InDonEsiA journaL Information System, 2024)
Higher Education Service Institutions (LLDIKTI) Region IV West Java and Banten require a web-based Geographic Information System (WebGIS) that provides information about Private Universities (PTS) in West Java and Banten with a search feature that can provide recommendations for the distance of the closest PTS to the location user. Based on this, the author aims to create a WebGIS that applies the Haversine formula in the nearest PTS search feature so that it can help people who have difficulty finding information about PTS in West Java and Banten. In this case, PTS mapping uses Quantum GIS (QGIS) software which is then integrated with the mapping results on the web with Google Maps. The system development method used in this research is Rapid Application Development (RAD) using the CodeIgniter 3 framework and system design using Unified Modeling Language (UML) including Use Case Diagrams and Activity Diagrams. The system testing in this research uses Usability Testing, with system testing by users in 3 different cities. The WebGIS created by the author succeeded in providing detailed PTS information, and the Haversine formula was successfully applied in the search feature to display search results based on recommendations for the distance of the closest PTS to the user's location. This system requires location access permission on the user's device so that the system can detect the user's location as a calculation material in determining the closest distance.